The Effect Of Quizizz On Students Reading Comprehension - Intan Hamzah (Faculty of Arts and Education, 2023)
The aim of this research is to investigate the relationship between mobile-assisted language learning and vocabulary learning integrated with the Quizizz platform. The researcher opted to examine the major effect of employing Mobile-Assisted Language Learning (MALL) coupled with Quizizz on Reading Comprehension of Senior High School students at SMA Negeri 13 Bandar Lampung based on the preceding considerations. This research study used a quantitative approach. The conclusion is based on the presentation and description of the findings and discussions from the data analysis. There was an increase in students' scores on the pre-test and post-test. Online learning using Quizizz towards English students' reading comprehension at SMA Negeri 13 Bandar Lampung is quite effective when viewed from student learning outcomes. Student learning outcomes after lectures using Quizizz are higher than student learning outcomes before studying.Keywords: Mobile-Assisted Language Learning, Quizizz, Reading Comprehension